2009
DOI: 10.1038/ijo.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

Overweight children have higher circulating hepcidin concentrations and lower iron status but have dietary iron intakes and bioavailability comparable with normal weight children

Abstract: Background: Obesity increases the risk for iron deficiency, but the underlying mechanism is unclear. It is possible that overweight individuals may have lower dietary iron intake and/or bioavailability. Alternatively, obesity-related inflammation may increase hepcidin concentrations and reduce iron availability. Circulating hepcidin levels have not been compared in normal weight vs overweight individuals. Objective: The objective of this study was to compare iron status, dietary iron intake and bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
156
4
19

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(200 citation statements)
references
References 38 publications
21
156
4
19
Order By: Relevance
“…The presented study confirmed an inverse correlation between CRP and iron level, although the hepcidin level was not assessed. Similar to the results obtained by Yanoff, a positive correlation between C-reactive protein and BMI was found in the current study, confirming that obesity is associated with a low-grade inflammatory status that promotes release of acute-phase molecules [10,22].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presented study confirmed an inverse correlation between CRP and iron level, although the hepcidin level was not assessed. Similar to the results obtained by Yanoff, a positive correlation between C-reactive protein and BMI was found in the current study, confirming that obesity is associated with a low-grade inflammatory status that promotes release of acute-phase molecules [10,22].…”
Section: Discussionsupporting
confidence: 92%
“…The responsible mechanism is not fully understood, but it is believed that an increased level of pro-inflammatory cytokines, such as C-reactive protein, activates hepcidin expression, consecutively leading to restriction in intestinal iron absorption and macrophage iron release through hepcidin downregulating influence on ferroportin-1 [22]. It is thought that hepcidin inhibits expression of ferroportin 1, limiting iron absorption in duodenum, and iron ex-flux from cells to the plasma [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results support the data reported in some articles showing that obese patients have higher circulating hepcidin concentrations compared to normal weight subjects and corroborate the idea that the poor iron status frequently observed in obese children may be due to the hepcidin-mediated inhibition of dietary iron absorption. [6][7][8] Recently, in a group of obese women subjected to restrictive bariatric surgery, in agreement with our results, after weight loss, decreased serum hepcidin and improved functional iron status has been shown. 15 We also observed that change in hepcidin concentrations was associated with change in leptin independently of BMI.…”
Section: Discussionsupporting
confidence: 91%
“…4,5 Three recent studies have shown that, both in obese women and in obese children, serum hepcidin levels were significantly higher compared with normal weight controls and have focused on the hepcidin-mediated inhibition of dietary iron absorption in obese patients. [6][7][8] To gain insight into the link between obesity and hepcidin, we performed an intervention study in a group of obese children and evaluated if body mass index (BMI) decrease may reduce circulating hepcidin levels, increasing, therefore, iron absorption and improving iron status.…”
Section: Introductionmentioning
confidence: 99%